2010
DOI: 10.1007/s11145-010-9281-8
|View full text |Cite
|
Sign up to set email alerts
|

Semantic and plausibility effects on preview benefit during eye fixations in Chinese reading

Abstract: The boundary paradigm (Rayner, 1975) was used to examine whether high level information affects preview benefit during Chinese reading. In two experiments, readers read sentences with a 1-character target word while their eye movements were monitored. In Experiment 1, the semantic relatedness between the target word and the preview word was manipulated so that there were semantically related and unrelated preview words, both of which were not plausible in the sentence context. No significant differences betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
109
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(136 citation statements)
references
References 50 publications
23
109
4
Order By: Relevance
“…Indeed, Yan et al (2009) demonstrated semantic PB using simple Chinese characters as previews. Later studies extended this effect to other character sets (Tsai, Kliegl, & Yan, 2012;Yan, Zhou, Shu, & Kliegl, 2012;Yang, Wang, Tong, & Rayner, 2012).…”
mentioning
confidence: 83%
“…Indeed, Yan et al (2009) demonstrated semantic PB using simple Chinese characters as previews. Later studies extended this effect to other character sets (Tsai, Kliegl, & Yan, 2012;Yan, Zhou, Shu, & Kliegl, 2012;Yang, Wang, Tong, & Rayner, 2012).…”
mentioning
confidence: 83%
“…The findings above suggest that parafoveal processing depends on the amount of resources left over from requisite 8 See also Yang, Wang, Tong and Rayner (2010) for some further evidence of semantic preview benefit in Chinese. 9 Hohenstein et al (2010) argued that the lack of a semantic preview benefit in most studies is due to the previews' appearing for longer than 125 ms and that such studies do not precisely control for preview duration.…”
Section: Parafoveal Processing Depends On Attentionmentioning
confidence: 94%
“…Of note, predictability and integrability are correlated; words can be highly predictable and easily integrated. However, words can also have low predictability and be easily integrated with a given context (Yang, Wang, Tong, & Rayner, 2012). To test predictability effects, two conditions with words that had high predictability or low predictability given a single context sentence were used.…”
Section: Current Experimentsmentioning
confidence: 99%